2003
DOI: 10.1002/neu.10259
|View full text |Cite
|
Sign up to set email alerts
|

Different regulation of Purkinje cell dendritic development in cerebellar slice cultures by protein kinase Cα and ‐β

Abstract: Activity of protein kinase C (PKC), and in particular the PKCgamma-isoform, has been shown to strongly affect and regulate Purkinje cell dendritic development, suggesting an important role for PKC in activity-dependent Purkinje cell maturation. In this study we have analyzed the role of two additional Ca(2+)-dependent PKC isoforms, PKCalpha and -beta, in Purkinje cell survival and dendritic morphology in slice cultures using mice deficient in the respective enzymes. Pharmacological PKC activation strongly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 37 publications
(52 reference statements)
3
27
0
Order By: Relevance
“…In addition to its effects on ␥-Pcdh function shown here, PKC is well known to be a negative downstream regulator of dendrite arborization (9,34,35,38,39). Consistent with this, broad activation of PKC by PMA reduced arborization to low levels regardless of which construct was expressed (Fig.…”
Section: Phosphorylation Of Ser-922 Disrupts ␥-Pcdh Inhibition Of Butsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition to its effects on ␥-Pcdh function shown here, PKC is well known to be a negative downstream regulator of dendrite arborization (9,34,35,38,39). Consistent with this, broad activation of PKC by PMA reduced arborization to low levels regardless of which construct was expressed (Fig.…”
Section: Phosphorylation Of Ser-922 Disrupts ␥-Pcdh Inhibition Of Butsupporting
confidence: 79%
“…In support of this, although Gö6983 treatment did not enhance branching further in neurons expressing A3-S/A, PMA did reduce branching to low levels in these neurons. In any case, PKC is known to regulate dendrite arborization in multiple neuronal subtypes (34,35,38,39); given the widespread neural expression of the ␥-Pcdhs (9, 17, 21), our identification of Ser-922 as a PKC target may thus have broad relevance to PKC signaling and dendrite development throughout the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The ␣ and ␤ isoforms are broadly expressed in the brain throughout life and play important roles in such fundamental functions as neurotransmitter release, synaptic plasticity, neurite development, and the regulation of neurotransmitter receptor clustering and internalization (Cambray-Deakin et al, 1990;Ben-Shlomo et al, 1991;Coffey et al, 1993;Brandon et al, 1999;Fan et al, 2002;Gundlfinger et al, 2003;Leitges et al, 2004;Tatsukawa et al, 2006) (for review, see Tanaka and Saito, 1992;Silinsky and Searl, 2003). In contrast, the ␥ isoform of PKC is expressed in only a few specific types of neurons in the brain, such as the Purkinje cells in the cerebellum, pyramidal and granule cells in the hippocampus, and lamina II neurons in the dorsal horn of the spinal cord Tanaka and Saito, 1992;Van Der Zee et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…PRKCB1-2 is most predominantly found in the synaptic endings of the parallel fibers of the granule cells. 42 This isoform of the protein kinase C family plays a central role in the regulation of synaptic transmission. 51 56 showed that granule neurons play a role in Purkinje cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Results were consistent over all analysis programs with comparable significance levels (P ¼ 0.005 for TDTPHASE and P ¼ 0.002 for PDTPHASE, respectively). The three most positive SNPs 128, 136 (hCV11192725) and 140 (hCV946275) are all intragenic for the PRKCB1 gene, which plays a vital role in the regulation of synaptic function, 42 making it a reasonable positional and functional candidate. Another single SNP (SNP 73, hCV789442) located within the OTOA gene also showed a nominal significant Pvalue (P ¼ 0.01).…”
Section: Linkage Analysesmentioning
confidence: 99%